Recent Dutch and Belgian Approaches to Ethnicity in Africa - Schilder, Kees; Van Binsbergen, Wim (Afrika Focus, 1993)
The papers in the present special issue of Afrika Focus are discussed from a comparative and theoretical perspective, which highlights the shortcomings of current approaches to African ethnicity on two counts: the assumption that ethnicity is a colonial creation, and the over-emphasis on political manipulation. The papers here presented suggest that there is a case for a re-assessment of the limits to ethnic manipulation, and the exploration of the explanatory value of local cultures considered over considerable time periods. KEY WORDS : ethnicity, Africa, colonialism, culture